Technology of functional cereal products - Hamaker, Bruce R. (Woodhead Publishing in food science, technology, and nutrition., 2008)
Cereal grains and their fractions contain many health-protecting compounds such as phytochemicals, vitamins and indigestible carbohydrates, but the texture and taste of functional cereal products can be less than ideal. This important collection reviews technologies for producing a wide range of cereal products with different health-promoting properties and more acceptable sensory quality. The first part of the book discusses the health effects of cereals, with chapters on topics such as whole grain foods, cereal micronutrients and resistant starch. Consumer perception of health-promoting cereal products and regulatory and labelling issues are also described. The second part focuses on technologies to improve the quality of functional cereal products, reviewing issues such as grain improvement, novel cereal-derived ingredients and formulation of low GI products. Chapters dedicated to a wide range of product types are also included, covering cereal foods made from oats, rye, barley and speciality grains and breads fortified with vitamins and minerals, soy and omega-3 lipids among others. Technology of functional cereal products is an essential reference for all those involved in research and development of health-promoting cereal-based foods. Reviews technologies for producing a wide range of cereal productsDiscusses the health effect of cereals, including whole grain foods and cereal micronutrientsDescribes consumer perception of health promoting cereal products.